2019
DOI: 10.5513/jcea01/20.1.2191
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and quality of two-row winter barley cultivars on an acid soil

Abstract: The experiment was established at the experimental field of the Dr. Đorđe Radić Secondary School of Agriculture and Chemistry in Kraljevo (Serbia) during the 2010/11, 2011/12 and 2012/13 growing seasons. The objective of the research was to evaluate the effect of genotype and the environment on the grain yield of winter barley cultivars ('Jagodinac', 'Maksa', 'Rekord', 'NS 565' and 'NS 525'). The following characteristics were analysed: grain yield, 1,000 grain weight, test weight and plant height. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The correlative dependence indicated that the grain yield in all vegetation seasons was positive and highly significantly correlated with test weight, except in the 2017/18 season where a significant correlation was established. A positive and significant correlation of grain yield and test weight of winter triticale in vegetation season has been established by Đekić et al (2014) andTerzic et al (2018) (r = 0.44 * or r = 0.49 * ). A negative and highly significant correlation between grain yield and test weight of winter triticale (r = -0.64 ** ) has been established by Rajičić et al (2020a).…”
Section: Correlations Between the Analysed Traitsmentioning
confidence: 78%
See 2 more Smart Citations
“…The correlative dependence indicated that the grain yield in all vegetation seasons was positive and highly significantly correlated with test weight, except in the 2017/18 season where a significant correlation was established. A positive and significant correlation of grain yield and test weight of winter triticale in vegetation season has been established by Đekić et al (2014) andTerzic et al (2018) (r = 0.44 * or r = 0.49 * ). A negative and highly significant correlation between grain yield and test weight of winter triticale (r = -0.64 ** ) has been established by Rajičić et al (2020a).…”
Section: Correlations Between the Analysed Traitsmentioning
confidence: 78%
“…Positive and significant correlations of grain yield and 1000-grain weight in fertilization have been established by Rajičić et al (2020a). A negative and not-significant correlation between grain yield and 1000-grain weight of winter triticale has been established by Đekić et al (2014) andTerzić et al (2018).…”
Section: Correlations Between the Analysed Traitsmentioning
confidence: 95%
See 1 more Smart Citation
“…Triticale's capacity to absorb nutrients during the growth season is influenced by the height of the yield and the size of the vegetative organs. The most typical nitrogen applications in Serbia vary from 80 to 120 kg ha -1 , depending on the agrochemical characteristics of the soil (Đekić et al, 2014;Terzic et al, 2018;Rajičić et al, 2020a). Large volumes of fertilizers can reduce yields and be detrimental to the environment and the economy, which is a major cause of agroecosystem pollution (Đekić et al, 2016;Rajičić et al, 2019;Madić et al, 2020;Tmušić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Large volumes of fertilizers can reduce yields and be detrimental to the environment and the economy, which is a major cause of agroecosystem pollution (Đekić et al, 2016;Rajičić et al, 2019;Madić et al, 2020;Tmušić et al, 2021). Weather and particular site conditions have a big impact on how well fertilizers are used and how much produce is produced (Đekić et al, 2014;Đurić et al, 2016;Madić et al, 2018;Terzić et al, 2018;Rajičić et al, 2021). Effective nitrogen fertilization is essential for producing grains profitably, as well as safeguarding groundwater and surface waters from contamination brought on by nitrate leaching as a result of excessive and insufficient nitrogen application (Todorović and Filipović, 2009;Biberdžić et al, 2012;Babić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%